Development of size-tunable polymeric nanoparticles for drug delivery applications - Sawasdee, Komkrich; Choksawad, Ployphailin; Pimcharoen, Sopida; Prapainop, Kanlaya (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Poly lactide-co-glycolide (PLGA) nanoparticles (NPs) have been widely used in drug delivery applications because of their excellent properties such as biocompatibility, and biodegradability along with the ability to deliver hydrophobic drugs, increase drug bioavailability and improve drug absorption to targeted cells in both oral and parenteral administrations. The PLGA NPs can be synthesized using an emulsion solvent evaporation method. Each parameter during synthesis plays a role in the formation of nanoparticles and can affect NP size; important factors for successful development of a drug delivery system.Aims: The aim of this study was to prepare different sizes of PLGA NPs by investigation of four factors (molecular weight, MW) of PLGA, emulsifier concentrations, organic solvent type and power of ultrasonication) involved in PLGA nanoparticle synthesis.Methods: PLGA nanoparticles were prepared by an emulsion solvent evaporation method. Size and size distribution were analyzed by dynamic light scattering and polydispersity index (PdI).Results: The effect of four parameters: PLGA MW, emulsifier concentrations, solvent types, and amplitude of ultrasonication on PLGA NPs preparation were evaluated. Changing one parameter results in different sizes of PLGA NPs that varied from 150- 300 nm. PdI which is an indicator for determination of size distribution of NPs, varied with an overall value <0.2.Conclusion: MW of PLGA polymer, emulsifier concentration, type of organic solvent and power of ultrasonication affect the size and size distribution of PLGA NPs. Submitted: 16 October 2017, Accepted: 27 October 2017. DOI: https://doi.org/10.35898/ghmj-12113